2021
DOI: 10.1186/s12868-021-00652-1
|View full text |Cite
|
Sign up to set email alerts
|

The disrupted topological properties of structural networks showed recovery in ischemic stroke patients: a longitudinal design study

Abstract: Introduction Stroke is one of the leading causes of substantial disability worldwide. Previous studies have shown brain functional and structural alterations in adults with stroke. However, few studies have examined the longitudinal reorganization in whole-brain structural networks in stroke. Methods Here, we applied graph theoretical analysis to investigate the longitudinal topological organization of white matter networks in 20 ischemic stroke pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…The example of application presented in this study highlighted the impact of graph-based metrics in connectivity analysis. Both local and global metrics derived from the whole-brain networks of Case 1 and Case 2 differed from HC one, as expected ( Crofts et al, 2011 ; Cheng et al, 2019 ; Li et al, 2021 ). This quantitative result mirrored the differences qualitatively observed with connectograms.…”
Section: Discussionsupporting
confidence: 79%
“…The example of application presented in this study highlighted the impact of graph-based metrics in connectivity analysis. Both local and global metrics derived from the whole-brain networks of Case 1 and Case 2 differed from HC one, as expected ( Crofts et al, 2011 ; Cheng et al, 2019 ; Li et al, 2021 ). This quantitative result mirrored the differences qualitatively observed with connectograms.…”
Section: Discussionsupporting
confidence: 79%
“…The research of Nierhaus and colleagues has showed increased functional connectivity between the caudate nucleus and red nucleus in patients with poststroke motor disturbance [ 47 ]. Li et al who used graph-based theoretical approach found that the nodal efficiency of acute stroke patients with unimanual motor deficits was reduced in the caudate [ 48 ]. However, correlation results in the current study showed that there was a significant negative correlation between FMA scores and fALFF value of the right caudate.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging technics allow the description of network reorganización after a stroke. The majority of recent studies report the conservation of small-world definition for the network state, but with a deterioration of specific small-world indices in acute ( Caliandro et al, 2017 ; Shi et al, 2021 ) and subacute stages of the stroke ( Wang et al, 2010 ; Zhang et al, 2017 ; Li et al, 2021 ). Interestingly, the preservation ( Bonilha et al, 2016 ) and recovery ( Caliandro et al, 2017 ; Li et al, 2021 ) of optimal small-world properties of the network correlate positively with the improvement of cognitive and motor functions, suggesting that small-world indices restoration could be a proxy for predicting neurological recovery ( Vecchio et al, 2019 ).…”
Section: Energy and Neural Networkmentioning
confidence: 99%
“…The majority of recent studies report the conservation of small-world definition for the network state, but with a deterioration of specific small-world indices in acute ( Caliandro et al, 2017 ; Shi et al, 2021 ) and subacute stages of the stroke ( Wang et al, 2010 ; Zhang et al, 2017 ; Li et al, 2021 ). Interestingly, the preservation ( Bonilha et al, 2016 ) and recovery ( Caliandro et al, 2017 ; Li et al, 2021 ) of optimal small-world properties of the network correlate positively with the improvement of cognitive and motor functions, suggesting that small-world indices restoration could be a proxy for predicting neurological recovery ( Vecchio et al, 2019 ). Studies in animal models ( van Meer et al, 2012 ) have complemented these findings, showing that the initial small-worldness (an excessive clustering and wiring of the network) evolves to an optimal small-world topology in the chronic stage.…”
Section: Energy and Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation